Solutions of a Generalization of Linear Volterra Integro-Differential Equations - Inpoonjai, Phaisatcha (Journal of the Indonesian Mathematical Society, 2026)
In this paper, we combine linear Volterra integro-differential equations of first and second kinds to be a generalization. Then, we use Laplace transform to solve an analytical solution on a convolution kernel and apply Laguerre polynomials to approximate a solution on a non-convolution kernel of this generalization.